1984
DOI: 10.1111/j.1600-0536.1984.tb00935.x
|View full text |Cite
|
Sign up to set email alerts
|

Contact and photocontact allergy in persistent light reactivity

Abstract: The patient group consisted of 18 elderly male patients with persistent light reactivity who were subjected to extensive phototesting with different wavelengths, including patch and photopatch testing. All reacted adversely to ultraviolet light and some also to longer wavelengths when tested on normal appearing skin. 17 patients showed contact or photocontact reactions, of which 12 were positive photopatch test reactions and 11 were plain contact reactions. Contact allergy to constituents of oak moss and diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

1991
1991
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(11 citation statements)
references
References 24 publications
(31 reference statements)
0
11
0
Order By: Relevance
“…This is in contrast to some literature which suggested that PA was more common in conditions such as PLE. 1,23,24 In addition, 42 of the 65 patients with UVA photosensitivity were not known to be UVA sensitive prior to testing and were only detected as a direct result of UVA MED testing being performed during PPT.…”
Section: Discussionmentioning
confidence: 99%
“…This is in contrast to some literature which suggested that PA was more common in conditions such as PLE. 1,23,24 In addition, 42 of the 65 patients with UVA photosensitivity were not known to be UVA sensitive prior to testing and were only detected as a direct result of UVA MED testing being performed during PPT.…”
Section: Discussionmentioning
confidence: 99%
“…It is present in many after-shave preparations, colognes, perfumes, hair sprays, hair creams, shampoos, soaps, deodorants and also in perfumed topical medica tions [17], Because the patient was unable to remember the brands of perfumes and colognes he had used, it was impossible to determine the source of musk ambrette. The association of contact allergy to fragrance mix in our patient was not surprising, because a high incidence of contact allergies among patients with persistent light reac tion was reported [6], This may reflect a greater suscepti bility towards sensitization in such patients.…”
Section: Discussionmentioning
confidence: 91%
“…Subsequently, more cases of PACD caused by other photoallergens like olaquindox and musk ambrette were reported (5)(6)(7)(8)(9). Although persistent light reactivity was also reported with other agents including musk ambrette, hexachlorophene, olaquindox, and ketoprofen (10,11), this entity is now considered a part of CAD spectrum (12)(13)(14)(15)). An association between PACD and CAD exists; however, the underlying mechanisms are unknown and there is little evidence to support a causal relationship (16).…”
Section: Historymentioning
confidence: 92%